Rutin and Gallic Acid Regulates Mitochondrial Functions via the SIRT1 Pathway in C2C12 Myotubes - Chang, Wei-Tang; Huang, Shih-Chien; Cheng, Hsin-Lin; Chen, Shiuan-Chih; Hsu, Chin-Lin (Antioxidants, 2021)
Mitochondria are highly dynamic organelles, balancing synthesis and degradation in response to increases in mitochondrial turnover (i.e., biogenesis, fusion, fission, and mitophagy) and function. The aim of this study was to investigate the role of polyphenols in the regulation of mitochondrial functions and dynamics in C2C12 myotubes and their molecular mechanisms. Our results indicate that gallic acid and rutin are the most potential polyphenol compounds in response to 15 phenolic acids and 5 flavonoids. Gallic acid and rutin were associated with a significantly greater mitochondrial DNA (cytochrome b and COX-II), mitochondrial enzymatic activities (including citrate synthase and cytochrome c oxidase), and intracellular ATP levels in C2C12 myotubes. Moreover, gallic acid and rutin significantly increased the gene expressions of mitochondrial turnover in C2C12 myotubes. Our findings indicated that gallic acid and rutin may have a beneficial effect on mitochondrial dynamics via regulation of the SIRT1-associated pathway in C2C12 myotubes.